Sexual harassment: how far does the penal code protect the victim? - Anita Abdul Rahim, (Fakulti Undang - Undang, 2000)

(untitled)
Sexual harassment comes in various form such as offensive remarks or jokes, showing off pornographic materials, sex-based letters etc. These series of act are not only evident against women, but sometimes it is prejudiced against men as well. More recently, attention has been given to this serious problem of sexual harassment, either in a workplace or even in other places. The question here is, do we have a specific legislation or law to address the problem of sexual harassment and to buttress the commission of this particular offence? This article is aimed at highlighting the relevant provisions of law relating to sexual harassment and discussing the problems that arise in enforcing the law. Lastly in this article it may also be useful to consider the effectiveness of the existing law in protecting the victims and the public at large. This is significant to be noted because law is the only instrument through which crimes can be prevented: provided the law enforcement machinery implements the provisions of law efficiently